2010
DOI: 10.2355/isijinternational.50.822
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of P2O5 between Solid Solution of 2CaO·SiO2–3CaO·P2O5 and Liquid Phase

Abstract: Fig. 15. Relation between the distribution ratio of P 2 O 5 and the CaO content of the liquid at different (log g P 2 O 5 ,SS ) cal .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 8 publications
4
72
0
2
Order By: Relevance
“…It was also interesting to note that the central part of the polygonal grey crystal (phase A) (Fig. 7(b)) mainly consisted of CaO and SiO 2 , which can be identified as 2CaO·SiO 2 , i.e., the main part of nC 2 S-C 3 P solid solution, 20,21) as shown in Table 2. However, with the addition of CaF 2 , it can be clearly observed that the primary crystal was typical bar-type structure.…”
Section: Identification Of Crystalline Phasesmentioning
confidence: 99%
“…It was also interesting to note that the central part of the polygonal grey crystal (phase A) (Fig. 7(b)) mainly consisted of CaO and SiO 2 , which can be identified as 2CaO·SiO 2 , i.e., the main part of nC 2 S-C 3 P solid solution, 20,21) as shown in Table 2. However, with the addition of CaF 2 , it can be clearly observed that the primary crystal was typical bar-type structure.…”
Section: Identification Of Crystalline Phasesmentioning
confidence: 99%
“…A escória de desfosforação é normalmente composta de um sistema CaO-SiO2-FeO-P2O5, sendo de conhecimento que a formação da fase sólida silicato dicálcio (2CaO.SiO2) tem papel de grande importância por formar uma solução sólida com o principal produto da desfosforação, o 3CaO.P2O5. Estes formam uma solução sólida de 2CaO.SiO2-3CaO.P2O5 com a escória liquida [5]. A formação do 2CaO.SiO2-3CaO.P2O5 ocorre na interface entre o sólido 2CaO.SiO2 e a escória.…”
Section: Introductionunclassified
“…A formação do 2CaO.SiO2-3CaO.P2O5 ocorre na interface entre o sólido 2CaO.SiO2 e a escória. Portanto, o estudo dos mecanismos de formação dessas fases sólidas se torna importante para o entendimento completo da sua atuação no processo [5]. Através da dissolução da cal pela escória líquida ocorre a formação de fases sólidas como o silicato dicálcio (2CaO.SiO2), silicato tricálcio (3CaO.SiO2) e cálcio-ferrita (CaO.FexO).…”
Section: Introductionunclassified
“…Even so, it can be safely assumed that the primary phase that precipitates during cooling is 2CaOÁSiO 2 , and that this phase will separate with the FeO-rich liquid phase. It is known that the distribution of phosphorus in the 2CaOÁSiO 2 phase is higher than in the liquid slag phase [5][6][7][8][9][10][11][12][13][14]. If it is possible to separate the solid 2CaOÁSiO 2 phase that includes P 2 O 5 with the FeO-rich liquid phase, it will be possible to use these phases as sources of phosphorus and iron.…”
Section: Introductionmentioning
confidence: 99%